Effectiveness, safety, and costs of thromboprophylaxis with enoxaparin or unfractionated heparin in inpatients with obesity - Amin, Alpesh; Kartashov, Alex; Ngai, Wilson; Steele, Kevin; Rosenthal, Ning (Frontiers in Cardiovascular Medicine, 2023)
Background: Obesity is a frequent and significant risk factor for venous thromboembolism (VTE) among hospitalized adults. Pharmacologic thromboprophylaxis can help prevent VTE, but real-world effectiveness, safety, and costs among inpatients with obesity are unknown. Objective: To compare clinical and economic outcomes among adult inpatients with obesity who received thromboprophylaxis with enoxaparin or unfractionated heparin (UFH). Methods: A retrospective cohort study was performed using the PINC AI™ Healthcare Database, which covers more than 850 hospitals in the United States. Included patients were ≥18 years old, had a primary or secondary discharge diagnosis of obesity (International Classification of Diseases [ICD]-9 diagnosis codes: 278.01, 278.02, 278.03; ICD-10 diagnosis codes: E66.0x, E66.1, E66.2, E66.8, E66.9), received >1 thromboprophylactic dose of enoxaparin (≤40 mg/day) or UFH (≤15,000 IU/day) during index hospitalization, stayed >6 days in the hospital, and were discharged between January 1, 2010 and September 30, 2016. Multivariable regression models were constructed to compare enoxaparin with UFH based on incidence of VTE, pulmonary embolism (PE)-related mortality, overall in-hospital mortality, major bleeding, treatment costs, and total hospitalization costs during the index hospitalization and the 90 days after index discharge (readmission period). Results: Among 67,193 inpatients who met selection criteria, 44,367 (66%) received enoxaparin and 22,826 (34%) received UFH during their index hospitalization. Demographic, visit-related, clinical, and hospital characteristics differed significantly between groups. Enoxaparin during index hospitalization was associated with 29%, 73%, 30%, and 39% decreases in the adjusted odds of VTE, PE-related mortality, in-hospital mortality, and major bleeding, respectively, compared with UFH (all p < 0.002). Patients who received enoxaparin also had lower adjusted odds of VTE and major bleeding during the readmission period compared with patients who had received UFH, with a trend toward statistical significance (adjusted odds ratios, 0.88 and 0.85, respectively; upper limit of each 95% CI, 1.0). Compared with UFH, enoxaparin was associated with significantly lower total hospitalization costs during the index hospitalization and readmission periods. Conclusions: Among adult inpatients with obesity, primary thromboprophylaxis with enoxaparin compared with UFH was associated with significantly lower rates of in-hospital VTE, major bleeding, PE-related mortality, and overall in-hospital mortality, and significantly lower hospitalization costs.